Coconut shell biomass hard carbon material for negative electrode of sodium ion battery and preparation method of coconut shell biomass hard carbon material
Through the preparation of coconut shell biomass hard carbon material, the problem that graphite materials in sodium ion batteries are difficult to accommodate sodium ions is solved, and a sodium ion battery negative electrode material with high specific capacity and excellent circulation performance is achieved.
Patent Information
- Application Number
- CN202510076900.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The capacity performance of existing sodium ion batteries is insufficient and the cycle stability is poor, mainly due to the difficulty of traditional graphite materials to effectively accommodate and embed sodium ions.
Coconut shell biomass is used as raw material, and high-performance hard carbon materials are prepared by soaking alkali and acid liquid, flash drying, low-temperature preoxidation and Joule thermal method, which are used for the negative electrode of sodium ion batteries.
It improves the specific capacity and first-term effect of sodium ion batteries, significantly improves the circulation performance, and makes the application of sodium ion batteries more reliable and efficient.
Smart Images

Figure CN119612497A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a coconut shell biomass hard carbon material for a negative electrode of a sodium ion battery and a preparation method thereof. Background Art
[0002] Since the beginning of the new century, oil prices have remained high, and the pollution caused by fossil fuels has become increasingly serious. People urgently need to develop new green and environmentally friendly energy to supplement or even replace their dependence on fossil fuel energy. Although sodium-ion batteries have begun to show their prowess in the market in recent years, lithium-ion batteries still occupy the core of the market and are widely penetrated into all walks of life. However, the current shortage of lithium resources has prompted the industry to place high hopes on sodium-ion batteries. Because the raw material sodium has abundant reserves and low cost worldwide, and the working principle is similar to that of lithium-ion batteries, the exploration of new sodium-ion batteries has attracted much attention.
[0003] But challenges come with it. Sodium ions have a larger radius (about 0.1nm) than lithium ions (about 0.06nm). The graphite materials used in traditional lithium-ion batteries have narrow interlayer spacing and cannot effectively accommodate the insertion and extraction of sodium ions, which seriously restricts the capacity performance of sodium-ion batteries. Further studies have shown that it is difficult for sodium and graphite to form a stable intercalation structure. This thermodynamic instability excludes the possibility of graphite as a negative electrode material for sodium-ion batteries. Therefore, finding a suitable negative electrode material to overcome the bottlenecks of sodium-ion batteries in capacity retention and Coulomb efficiency has become an urgent problem to be solved in the scientific research community.
[0004] After years of unremitting exploration, hard carbon materials have emerged as the ideal commercial candidate for negative electrode materials for sodium-ion batteries due to their unique advantages. Unlike the lithium storage mechanism of graphite, the sodium storage mechanism of hard carbon is more complex and is still under in-depth research. Generally recognized mechanisms include intercalation, alloying, and conversion reactions. The rich internal structure of hard carbon, such as surface edges and defects, graphite layer gaps and micropores, etc., provides a variety of storage spaces for sodium ions. This feature makes it stand out among many candidate materials.
[0005] It is particularly noteworthy that hard carbon materials converted from biomass are not only abundant in resources, low in cost, and simple in process, but also show positive potential in improving the Coulombic efficiency and conductivity of sodium-ion batteries. Taking into account cost-effectiveness, environmental friendliness, and performance, biomass-derived carbon materials, with their unique structural plasticity and performance optimization space, coupled with the sustainability and environmental protection characteristics of raw materials, perfectly meet the market demand for sodium-ion battery materials, indicating their broad application prospects in the future energy storage field.
[0006] The patent with application number 202310296062.0 proposes a method for producing hard carbon negative electrode materials for sodium ion batteries. The method uses plant straw or plant husk as raw materials, and prepares the hard carbon negative electrode materials for sodium ion batteries through the steps of crushing, tubular furnace pre-carbonization, alkaline activation and tubular furnace secondary carbonization. The patent mainly improves the carbonization efficiency and effect by placing it in layers during secondary carbonization. However, the hard carbon material prepared by this method has insufficient specific capacity and the cycle stability needs to be further improved. Summary of the invention
[0007] In order to solve the above technical problems, the present invention proposes a coconut shell biomass hard carbon material for a sodium ion battery negative electrode and a preparation method thereof. The method has a simple process flow, low cost, and is environmentally friendly. The sodium ion battery assembled with the sodium ion battery negative electrode made of the coconut shell biomass hard carbon material of the present invention has the advantages of high specific capacity, significant improvement in first efficiency, excellent cycle performance, etc.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] One of the technical solutions of the present invention:
[0010] A method for preparing a coconut shell biomass hard carbon material comprises the following steps: soaking coconut shell powder in an alkaline solution and an acid solution, removing impurities, washing the coconut shell powder to a neutral state, and drying the coconut shell powder precursor by a flash evaporation method; and sequentially subjecting the coconut shell powder precursor to low-temperature pre-oxidation and Joule heat-based oxygen-free high-temperature pyrolysis treatment to obtain the coconut shell biomass hard carbon material.
[0011] The present invention firstly grinds the washed and dried coconut shell into powder by a wall breaking machine, and then soaks it in alkaline solution, so as to use alkaline to remove macromolecular organic matter in biomass materials, partially hydrolyze cellulose, hemicellulose and lignin, and increase the uncertainty of subsequent carbon materials; then, the alkaline solution is washed away with deionized water and then soaked in acid solution, so as to remove excess alkaline solution and etch the material by acid; then, the coconut shell powder washed to neutral is flash dried, so as to regulate the microstructure of hard carbon materials, and the precursor is fully dried in a short time by the flash method, so as to form a hard carbon material with stable structure and large specific surface area. Carbon materials can accommodate more sodium ions; at the same time, low-temperature pre-oxidation in a muffle furnace is used to reduce hydrogen bonds in the material, increase the uncertainty of the material, and release gas molecules in the material to increase the pore structure; finally, high-temperature pyrolysis is carried out by Joule heat method without oxygen (with protective gas), and the extremely fast heating mechanism of the Joule rapid heating furnace is used to better fix carbon and enhance the carbon skeleton structure, making the produced carbon more difficult to graphitize, and making it perform better in sodium ion batteries; thereby obtaining high-performance coconut shell-based hard carbon negative electrode materials, and the combination of Joule heat method and flash evaporation method has extremely high utilization efficiency, which greatly reduces the time required for preparation.
[0012] Furthermore, in the method for preparing coconut shell biomass hard carbon material, the temperature of the flash drying is 50-200° C. The flash drying process is carried out in a flash drying chamber.
[0013] Furthermore, in the method for preparing coconut shell biomass hard carbon material, the temperature of the low-temperature pre-oxidation is 200-450° C., and the time is 4-12 hours. The pre-oxidation process is carried out in a muffle furnace.
[0014] Furthermore, in the preparation method of coconut shell biomass hard carbon material, the temperature of the Joule heat method oxygen-free high temperature pyrolysis is 900-1500° C., and the time is 0.5-2 hours. The Joule heat method oxygen-free high temperature pyrolysis process is carried out in a Joule rapid heating furnace.
[0015] Furthermore, in the preparation method of coconut shell biomass hard carbon material, the acid solution used for soaking in alkaline solution and acid solution includes one or more of sulfuric acid, hydrochloric acid and hydrofluoric acid solution, the alkaline solution used includes one or more of sodium hydroxide, ammonia water and potassium hydroxide solution, and the concentration of the acid solution or alkaline solution is 0.2-6 mol / L.
[0016] Furthermore, during the soaking in alkaline solution and acid solution, the amount of coconut shell added to the acid / alkaline solution is 10-50wt%.
[0017] Furthermore, in the preparation method of coconut shell powder washed to neutrality, the drying is carried out in a blast drying oven, the drying temperature is 50-120° C., and the drying time is 12-72 hours.
[0018] The second technical solution of the present invention:
[0019] A coconut shell biomass hard carbon material is prepared according to the preparation method.
[0020] The third technical solution of the present invention:
[0021] The coconut shell biomass hard carbon material is used in preparing a negative electrode sheet of a sodium ion battery.
[0022] The fourth technical solution of the present invention:
[0023] A battery negative electrode sheet for a sodium ion battery comprises the coconut shell biomass hard carbon material. The coconut shell biomass hard carbon material is mixed with conductive carbon black and an adhesive, and stirred evenly to obtain an electrode slurry; the electrode slurry is applied on a current collector, dried and then rolled to obtain the negative electrode sheet.
[0024] Compared with the prior art, the present invention has the following advantages and technical effects:
[0025] (1) The method provided by the present invention can use a large amount of collected waste coconut shells as raw materials, which is low-cost and widely available, while taking environmental protection into account and realizing the recycling and reuse of organic waste.
[0026] (2) The process flow of the present invention is short and simple. The flash evaporation-Joule heat method is used in combination with the traditional hard carbon preparation method to greatly reduce the time cost of making hard carbon, which is conducive to industrialization.
[0027] (3) The coconut shell bio-hard carbon negative electrode material prepared by the present invention has excellent sodium storage capacity. In battery applications, sodium ions can be effectively deintercalated in the negative electrode. The sodium ion battery assembled from the prepared sodium ion battery negative electrode has the advantages of high specific capacity, significant improvement in first efficiency, and excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0029] Figure 1 The SEM images of the coconut shell bio-hard carbon materials prepared in Example 1 and Comparative Example 1, wherein A) and B) are SEM images of the coconut shell bio-hard carbon materials at different magnifications of Example 1, and C) and D) are SEM images of the coconut shell bio-hard carbon materials at different magnifications of Comparative Example 1;
[0030] Figure 2 The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Example 1 as the raw material;
[0031] Figure 3 The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Comparative Example 1 as the raw material;
[0032] Figure 4 The first three charge and discharge results of the sodium ion battery prepared in Example 1 and Comparative Example 1, wherein A)-C) respectively represent the first three charge and discharge results of the sodium ion battery prepared in Example 1, and D)-F) respectively represent the first three charge and discharge results of the sodium ion battery prepared in Comparative Example 1;
[0033] Figure 5 The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Example 2 as the raw material;
[0034] Figure 6 The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Example 3 as the raw material;
[0035] Figure 7The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Example 4 as raw material;
[0036] Figure 8 The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Comparative Example 2 as the raw material;
[0037] Fig. 9 The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Comparative Example 3 as the raw material;
[0038] Fig.10 The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Comparative Example 4 as the raw material;
[0039] Fig.11 This is the cycle curve of the sodium ion battery prepared using coconut shell bio-hard carbon material as raw material in Comparative Example 5. DETAILED DESCRIPTION
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0041] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] An embodiment of the present invention provides a method for preparing a coconut shell biomass hard carbon material, wherein coconut shell powder that has been soaked in an alkali solution and an acid solution, removed impurities and washed to a neutral state is dried using a flash evaporation method to obtain a coconut shell powder precursor, and the coconut shell powder precursor is sequentially subjected to low-temperature pre-oxidation and Joule heat-based oxygen-free high-temperature pyrolysis treatment to obtain the coconut shell biomass hard carbon material.
[0046] In the method for preparing coconut shell biomass hard carbon material in a preferred embodiment of the present invention, the steam temperature of the flash evaporation method is 50-200°C, and most preferably 180°C.
[0047] The flash drying process is carried out in a flash drying chamber. Flash drying can achieve the regulation of the microstructure of the hard carbon material, and the flash method can fully dry the precursor in a short time to form a hard carbon material with a stable structure and a large specific surface area, which can accommodate more sodium ions.
[0048] In the preparation method of coconut shell biomass hard carbon material in the preferred embodiment of the present invention, the temperature of the low-temperature pre-oxidation is 200-450°C, and the time is 0.5-2h. The pre-oxidation process is carried out in a muffle furnace. For example, the temperature of the low-temperature pre-oxidation can be 200°C, 250°C, 300°C, 350°C, 400°C or 450°C, and the time can be 4h, 6h, 8h, 10h or 12h. Within the above temperature and time range, the release of volatile substances in the biomass raw materials can be reduced, so that more carbon elements are retained in the solid product, and at the same time, the hydrogen bonds between cellulose, hemicellulose and lignin in the biomass material are broken, and some functional group oxidation gases escape, forming a rich pore structure, thereby increasing the yield and purity of hard carbon and electrochemical properties.
[0049] In the preparation method of coconut shell biomass hard carbon material in the preferred embodiment of the present invention, the temperature of the Joule heat method oxygen-free high-temperature pyrolysis is 900-1500°C, and the time is 0.5-2h. The Joule heat method oxygen-free high-temperature pyrolysis process is carried out in a Joule rapid heating furnace. For example, the temperature of the Joule heat method oxygen-free high-temperature pyrolysis can be 900°C, 1000°C, 1100°C, 1200°C, 1400°C or 1500°C, and the time can be 0.5h, 1h, 1.5h, 1.8h or 2h, and pore formation can be achieved within the above pyrolysis temperature and time range.
[0050] Firing under the condition of protective gas can firstly improve safety, and secondly effectively prevent oxidation of materials, provide a pure environment, and reduce the impact of impurities on hard carbon materials; appropriate temperature can improve the carbonization efficiency of materials, improve microstructure, increase porosity, increase specific surface area, and improve the stability of hard carbon. In the preparation method of coconut shell biomass hard carbon material in the preferred embodiment of the present invention, the acid solution used in the acid / alkali soaking includes one or more of sulfuric acid, hydrochloric acid and hydrofluoric acid solution, and the alkaline solution used includes one or more of sodium hydroxide, ammonia water and potassium hydroxide solution, and the concentration of the acid solution or alkaline solution is 0.2-6mol / L, preferably 2-6mol / L.
[0051] In a preferred embodiment of the present invention, the acid solution used for soaking in the alkaline solution and the acid solution includes one or more of sulfuric acid, hydrochloric acid and hydrofluoric acid solutions, the alkaline solution used includes one or more of sodium hydroxide, ammonia water and potassium hydroxide solution, the concentration of the acid solution or the alkaline solution is 0.2-6 mol / L, and the amount of coconut shell added to the acid / alkaline solution is 10-50wt%.
[0052] In the method for preparing coconut shell powder washed to neutrality in a preferred embodiment of the present invention, the drying is carried out in a blast drying oven at a temperature of 50-120° C. for a time of 6-72 hours.
[0053] The embodiment of the present invention also provides a coconut shell biomass hard carbon material, which is prepared according to the above preparation method.
[0054] The raw materials used in the embodiments of the present invention can be purchased commercially.
[0055] The embodiment of the present invention has no special limitation on the amount of the acid / alkaline solution used, and it only needs to immerse the raw materials.
[0056] The technical solution of the present invention is further illustrated by the following embodiments.
[0057] Example 1
[0058] (1) washing the coconut shell with deionized water, cutting it into small pieces (with a diameter of 1 cm-3 cm), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and then grinding it into powder with a wall breaking machine to obtain a coconut shell powder raw material (particle size <13 μm);
[0059] (2) Place the coconut shell powdered raw material in a 500 mL beaker, add deionized water to cover the sample and place in an 80° C. oil bath for 2 h, then transfer to a 2 mol / L NaOH solution, stir and soak at 60° C. for 2 h, wash until neutral, transfer to a 2 mol / L HCl solution, stir and soak at 60° C. for 2 h, wash until neutral;
[0060] (3) placing the washed neutral coconut shell powder in a flash drying chamber and flash drying at 180° C. to obtain a coconut shell powder precursor;
[0061] (4) transferring the obtained coconut shell powder precursor into a muffle furnace, heating it to 300° C. and keeping it at that temperature for 10 h, and pre-oxidizing it at low temperature to obtain pre-pyrolysis carbon;
[0062] (5) grinding the obtained pre-pyrolyzed carbon into powder, and passing it through a 1000 mesh sieve to obtain an intermediate;
[0063] (6) The obtained intermediate was transferred into a Joule rapid heating furnace filled with nitrogen, and the temperature was rapidly raised to 1300° C. and kept at that temperature for 2 h to prepare coconut shell biomass hard carbon material.
[0064] Example 2
[0065] (1) washing the coconut shell with deionized water, cutting it into small pieces (with a diameter of 1 cm-3 cm), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and then grinding it into powder with a wall breaking machine to obtain a coconut shell powder raw material (particle size <13 μm);
[0066] (2) Place the coconut shell powdered raw material in a 500 mL beaker, add deionized water to cover the sample and place in an 80°C oil bath for 2 h, then transfer to a 2 mol / L KOH solution, stir and soak at 60°C for 2 h, wash until neutral, transfer to a 2 mol / L H2SO4 solution, stir and soak at 60°C for 2 h, wash until neutral;
[0067] (3) placing the washed neutral coconut shell powder in a flash drying chamber and flash drying at 180° C. to obtain a coconut shell powder precursor;
[0068] (4) transferring the obtained coconut shell powder precursor into a muffle furnace, heating it to 400° C. and keeping it at that temperature for 6 h, and pre-oxidizing it at low temperature to obtain pre-pyrolysis carbon;
[0069] (5) grinding the obtained pre-pyrolyzed carbon into powder, and passing it through a 1000-mesh sieve to obtain an intermediate;
[0070] (6) The obtained intermediate was transferred into a Joule rapid heating furnace filled with nitrogen, and the temperature was rapidly raised to 900°C and kept at this temperature for 2 hours to prepare a coconut shell biomass hard carbon material.
[0071] Example 3
[0072] (1) washing the coconut shell with deionized water, cutting it into small pieces (with a diameter of 1 cm-3 cm), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and then grinding it into powder with a wall breaking machine to obtain a coconut shell powder raw material (particle size <13 μm);
[0073] (2) Place the coconut shell powdered raw material in a 500 mL beaker, add deionized water to cover the sample and place in an 80° C. oil bath for 2 h, then transfer to 2 mol / L NaOH, stir and soak at 60° C. for 2 h, wash until neutral, transfer to 2 mol / L HCl solution, stir and soak at 60° C. for 2 h, wash until neutral;
[0074] (3) placing the coconut shell powder washed to neutrality in a flash drying chamber and flash drying at 50° C. to obtain a coconut shell powder precursor;
[0075] (4) transferring the obtained coconut shell powder precursor into a muffle furnace, heating it to 450° C. and keeping it at that temperature for 12 h, and pre-oxidizing it at low temperature to obtain pre-pyrolysis carbon;
[0076] (5) grinding the obtained pre-pyrolyzed carbon into powder, and passing it through a 1000-mesh sieve to obtain an intermediate;
[0077] (6) The obtained intermediate was transferred into a Joule rapid heating furnace filled with nitrogen, and the temperature was rapidly raised to 1500°C and kept at that temperature for 2 h to prepare coconut shell biomass hard carbon material.
[0078] Example 4
[0079] (1) washing the coconut shell with deionized water, cutting it into small pieces (with a diameter of 1 cm-3 cm), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and then grinding it into powder with a wall breaking machine to obtain a coconut shell powder raw material (particle size <13 μm);
[0080] (2) Place the coconut shell powdered raw material in a 500 mL beaker, add deionized water to cover the sample and place in an 80° C. oil bath for 2 h, then transfer to 4 mol / L NaOH, stir and soak at 60° C. for 2 h, wash until neutral, transfer to 4 mol / L HCL solution, stir and soak at 60° C. for 2 h, wash until neutral;
[0081] (3) placing the coconut shell powder washed to neutrality in a flash drying chamber and flash drying at 180° C. to obtain a coconut shell powder precursor;
[0082] (4) The obtained coconut shell powder precursor is transferred into a muffle furnace, heated to 200° C. and kept at this temperature for 12 h, and pre-oxidized at low temperature to obtain pre-pyrolysis carbon;
[0083] (5) grinding the obtained pre-pyrolyzed carbon into powder, and passing it through a 1000-mesh sieve to obtain an intermediate;
[0084] (6) The obtained intermediate was transferred into a Joule rapid heating furnace filled with nitrogen, and the temperature was rapidly raised to 1000° C. and kept at this temperature for 2 h to prepare a coconut shell biomass hard carbon material.
[0085] Comparative Example 1
[0086] (1) washing the coconut shell with deionized water, cutting it into small pieces (with a diameter of 1 cm to 3 cm), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and grinding it into powder with a wall breaking machine to obtain a coconut shell powder raw material (particle size <13 μm);
[0087] (2) Place the coconut shell powdered raw material in a 500 mL beaker, add deionized water to cover the sample and place in an 80° C. oil bath for 2 h, then transfer to a 2 mol / L NaOH solution, stir and soak at 60° C. for 2 h, wash until neutral, transfer to a 2 mol / L HCl solution, stir and soak at 60° C. for 2 h, wash until neutral;
[0088] (3) placing the coconut shell powder washed to neutrality into a forced air drying oven and drying at 60° C. to obtain a coconut shell powder precursor;
[0089] (4) transferring the obtained coconut shell powder precursor into a muffle furnace, heating it to 550° C. and keeping it at that temperature for 8 h, and pre-oxidizing it at low temperature to obtain pre-pyrolysis carbon;
[0090] (5) grinding the obtained pre-pyrolyzed carbon into powder, and passing it through a 1000-mesh sieve to obtain an intermediate;
[0091] (6) The intermediate obtained was transferred into a tubular furnace filled with nitrogen, and the temperature was increased to 1300°C at a heating rate of 10°C / min and kept at that temperature for 10 h to prepare a coconut shell biomass hard carbon material.
[0092] Comparative Example 2
[0093] (1) washing the coconut shell with deionized water, cutting it into small pieces (with a diameter of 1 cm to 3 cm), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and grinding it into powder with a wall breaking machine to obtain a coconut shell powder raw material (particle size <13 μm);
[0094] (2) Place the coconut shell powdered raw material in a 500 mL beaker, add deionized water to cover the sample and place in an 80° C. oil bath for 2 h, then transfer to a 2 mol / L NaOH solution, stir and soak at 60° C. for 2 h, wash until neutral, transfer to a 2 mol / L HCl solution, stir and soak at 60° C. for 2 h, wash until neutral;
[0095] (3) placing the coconut shell powder washed to neutrality into a forced air drying oven and drying at 60° C. to obtain a coconut shell powder precursor;
[0096] (4) The obtained coconut shell powder precursor is placed in a muffle furnace, rapidly heated to 300° C. and kept at this temperature for 8 h, and pre-oxidized at low temperature to obtain pre-pyrolysis carbon;
[0097] (5) grinding the obtained pre-pyrolyzed carbon into powder, and passing it through a 1000-mesh sieve to obtain an intermediate;
[0098] (6) The obtained intermediate was transferred into a Joule rapid heating furnace filled with nitrogen, and the temperature was rapidly raised to 1300° C. and kept at that temperature for 2 h to prepare coconut shell biomass hard carbon material.
[0099] Comparative Example 3
[0100] (1) washing the coconut shell with deionized water, cutting it into small pieces (1 cm-3 cm in diameter), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and then grinding it into powder with a wall breaking machine to obtain a coconut shell powder raw material (particle size <13 μm);
[0101] (2) Place the coconut shell powdered raw material in a 500 mL beaker, add deionized water to cover the sample and place in an 80°C oil bath for 2 h, then transfer to a 0.1 mol / L ammonia solution, stir and soak at 60°C for 2 h, wash until neutral, transfer to a 0.1 mol / L HNO3 solution, stir and soak at 60°C for 2 h, wash until neutral;
[0102] (3) placing the coconut shell powder washed to neutrality in a flash drying chamber and flash drying at 120° C. to obtain a coconut shell powder precursor;
[0103] (4) The obtained coconut shell powder precursor is transferred into a muffle furnace, heated to 150° C. and kept at this temperature for 2 h, and pre-oxidized at low temperature to obtain pre-pyrolysis carbon;
[0104] (5) grinding the obtained pre-pyrolyzed carbon into powder, and passing it through a 1000-mesh sieve to obtain an intermediate;
[0105] (6) The intermediate obtained was transferred into a tubular furnace filled with nitrogen, and the temperature was increased to 1300°C at a heating rate of 10°C / min and kept at that temperature for 10 h to prepare a coconut shell biomass hard carbon material.
[0106] Comparative Example 4
[0107] The same as Example 1, except that in step (4), the obtained coconut shell powder precursor is transferred into a muffle furnace, heated to 150° C. and kept warm for 2 h, and low-temperature pre-oxidized to obtain pre-pyrolysis carbon.
[0108] Comparative Example 5
[0109] The same as Example 1, except that in step (6), the intermediate obtained is transferred into a Joule rapid heating furnace filled with nitrogen, and the temperature is rapidly raised to 2500° C. and kept for 2 h to prepare a coconut shell biomass hard carbon material.
[0110] Performance Testing
[0111] The SEM images of the coconut shell bio-hard carbon materials prepared in Example 1 and Comparative Example 1 are shown in Figure 1 , A) and B) in the figure are SEM images of the coconut shell bio-hard carbon material of Example 1 at different magnifications, and C) and D) are SEM images of the coconut shell bio-hard carbon material of Comparative Example 1 at different magnifications. It can be seen that the coconut shell bio-hard carbon material prepared in Example 1 has obvious defect structure and pore network structure, and is rich in wrinkles and has a large specific surface area, which is conducive to the storage of ions. Although the coconut shell bio-hard carbon material prepared in Comparative Example 1 has a smaller particle size, there is no obvious layered structure and etched defective hole structure on the surface, which reflects that the battery performance prepared with this as raw material will be lower than that of Example 1.
[0112] The coconut shell bio-hard carbon material prepared in the embodiment or comparative example is mixed with conductive carbon black (ketjen black) and a binder (PVDF, i.e. polyvinylidene fluoride) in a mass ratio of 8:1:1, and stirred evenly to obtain an electrode slurry; the obtained electrode slurry is applied on a current collector, dried and rolled to obtain a negative electrode sheet for a sodium ion battery, and the negative electrode sheet is further prepared into a sodium ion battery.
[0113] The prepared sodium ion battery was subjected to a charge and discharge test at a current density of 0.2 A / g. The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Example 1 as the raw material is shown in FIG. Figure 2 ,from Figure 2 It can be seen from the graph that the negative electrode sheet of the battery has good cycle stability and has a high capacity at a rate of 0.1C. The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Comparative Example 1 as raw material is shown in Figure 3 ,from Figure 3 It can be seen that the cycle stability of the negative electrode sheet of the battery is general, the first efficiency is much lower than that of Example 1, and the capacity is low at a rate of 0.1C.
[0114] The first three charge and discharge results of the sodium ion battery prepared in Example 1 are shown in Figure 4 A)-C), the first three charge and discharge results of the sodium ion battery prepared in Comparative Example 1 are shown in Figure 4 D)-F) in Figure 4 As can be seen from Figure A), at a rate of 0.1C, the first cycle has a specific capacity of 1009.67 mAh / g, and the subsequent cycles also have a specific capacity of about 500 mAh / g. The stability of the subsequent two cycles is also good. However, the capacity of comparative example 1 is extremely low and the cycle stability is also poor.
[0115] Using the same method, the sodium ion batteries prepared in Example 2-6 and Comparative Example 2-5 were charged and discharged at a current density of 0.2 A / g, and the results were as follows:
[0116] The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Example 2 as raw material is shown in Figure 5 ,Depend on Figure 5 It can be seen that in Example 2, the battery obtained by using KOH to treat the sample with alkali has good performance, and the capacity and cycle stability are acceptable, which may be due to the similar chemical properties of KOH and NaOH. However, KOH may be slightly more alkaline than NaOH, so it has a stronger etching effect on the material, affecting the stability of the carbon structure and making the cycle stability average.
[0117] The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Example 3 as raw material is shown in Figure 6 The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Example 4 as raw material is shown in Figure 7 ,Depend on Figure 6 , Figure 7 It can be seen that the batteries obtained from the coconut shell bio-hard carbon materials prepared in Examples 3 and 4 have good performance, and both the capacity and cycle stability are acceptable.
[0118] The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Comparative Example 2 as raw material is shown in Figure 8 ,Depend on Figure 8 It can be seen that comparative example 2 uses ordinary oven drying instead of flash drying. Since the flash drying rate is fast, the structure of the raw materials can be maintained better. Therefore, the battery performance of comparative example 2 is not as good as that of embodiment 1, and the capacity and cycle stability are average.
[0119] The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Comparative Example 3 as raw material is shown in Fig. 9 ,Depend on Fig. 9 It can be seen that in Comparative Example 3, the Joule rapid heating furnace is replaced by a traditional tubular furnace. In addition to the increased energy loss, the performance of the battery is also significantly reduced, and the capacity and cycle stability are poor.
[0120] The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Comparative Example 4 as raw material is shown in Fig.10 ,Depend on Fig.10 It can be seen that in Comparative Example 4, the pre-oxidation pyrolysis temperature is lowered, and the cellulose and hemicellulose in the material have not been pre-oxidized, resulting in fewer subsequent secondary high-temperature pyrolysis pore structures, and thus the battery cycle performance is average and the capacity is extremely poor.
[0121] The cycle curve of the sodium ion battery prepared using the coconut shell bio-hard carbon material of Comparative Example 5 as raw material is shown in Fig.11,Depend on Fig.11 It can be seen that because the secondary temperature is too high, reaching 2500°C, the material is severely graphitized, resulting in very low capacity.
[0122] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing coconut shell biomass hard carbon material, characterized in that: The coconut shell powder that has been soaked in alkali solution and acid solution, removed impurities and washed to neutral is dried by flash evaporation to obtain a coconut shell powder precursor. The coconut shell powder precursor is sequentially subjected to low-temperature pre-oxidation and Joule heat-based oxygen-free high-temperature pyrolysis treatment to obtain the coconut shell biomass hard carbon material.
2. The method for preparing coconut shell biomass hard carbon material according to claim 1, characterized in that: The flash drying temperature is 50-200°C.
3. The method for preparing coconut shell biomass hard carbon material according to claim 1, characterized in that: The temperature of the low-temperature pre-oxidation is 200-450° C., and the time is 4-12 hours.
4. The method for preparing coconut shell biomass hard carbon material according to claim 1, characterized in that: The temperature of the oxygen-free high-temperature pyrolysis by Joule heat method is 900-1500° C. and the time is 0.5-2 h.
5. The method for preparing coconut shell biomass hard carbon material according to claim 1, characterized in that: The acid solution used for soaking in the alkaline solution and the acid solution includes one or more of sulfuric acid, hydrochloric acid and hydrofluoric acid solutions, and the alkaline solution used includes one or more of sodium hydroxide, ammonia water and potassium hydroxide solutions. The concentration of the acid solution or the alkaline solution is 0.2-6 mol / L.
6. A coconut shell biomass hard carbon material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 5.
7. Use of the coconut shell biomass hard carbon material as claimed in claim 6 in preparing a negative electrode sheet for a sodium ion battery.
8. A negative electrode sheet for a sodium ion battery, characterized in that: The invention comprises the coconut shell biomass hard carbon material as claimed in claim 6, wherein the coconut shell biomass hard carbon material as claimed in claim 6 is mixed with conductive carbon black and an adhesive, and stirred evenly to obtain an electrode slurry; the electrode slurry is applied on a current collector, dried and then rolled to obtain the electrode slurry.
Citation Information
Patent Citations
Production method of sodium ion battery hard carbon negative electrode material
CN116354332A
Preparation method, application and preparation device of low-voltage and high-specific-capacity hard carbon
CN116443868A
Preparation method and application of biomass hard carbon negative electrode material of sodium-ion battery
CN116692858A
Biomass hard carbon negative electrode material and preparation method and application thereof
CN117208886A
Biomass hard carbon material for negative electrode of sodium ion battery and preparation method of biomass hard carbon material
CN117790732A